2022
DOI: 10.1029/2022gc010564
|View full text |Cite
|
Sign up to set email alerts
|

The Signature of Lithospheric Anisotropy at Post‐Subduction Continental Margins: New Insight From XKS Splitting Analysis in Northern Borneo

Abstract: Northern Borneo-broadly coextensive with the Malaysian state of Sabah-lies near the north-eastern edge of the present-day Sundaland block, in Southeast Asia (Figure 1). This block, bounded by the seismically active Sunda and Philippines subduction zones, represents the southern extent of the slow-moving (∼20 mm year −1 ) Eurasian plate (Simons et al., 1999;Argus et al., 2011). Like much of eastern Borneo, northern Borneo was accreted onto the eastern margin of Mesozoic Sundaland between the Late Cretaceous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Post-subduction foundering in the form of a lithospheric drip is therefore our favoured explanation (Figure 10). While there could be a possibility that the sub-vertical high-velocity perturbation of the SD is due to, or significantly enhanced, by radial anisotropy, a high-velocity anomaly in correspondence of the SD drip is present in the S-wave model, which is much less influenced by radial anisotropy (see also Bacon et al, 2022). This indicates that the high-velocity perturbation associated to the SD in our tomographic models is likely due to a combination of thermal and compositional anomalies.…”
Section: Lithospheric Foundering In Sempornamentioning
confidence: 99%
“…Post-subduction foundering in the form of a lithospheric drip is therefore our favoured explanation (Figure 10). While there could be a possibility that the sub-vertical high-velocity perturbation of the SD is due to, or significantly enhanced, by radial anisotropy, a high-velocity anomaly in correspondence of the SD drip is present in the S-wave model, which is much less influenced by radial anisotropy (see also Bacon et al, 2022). This indicates that the high-velocity perturbation associated to the SD in our tomographic models is likely due to a combination of thermal and compositional anomalies.…”
Section: Lithospheric Foundering In Sempornamentioning
confidence: 99%
“…There have been a number of previous geophysical studies that have included northern Borneo, many of which involve the generation of regional velocity models of southeast Asia from seismic imaging. Although limited in resolution, they consistently reveal a high velocity feature in the upper mantle at around ∼100-300 km depth, which is generally attributed to remnant slabs Wehner et al, 2022;. More recently, targeted seismic studies have been performed using data from the northern Borneo Orogeny Seismic Survey (nBOSS) experiment .…”
Section: Introductionmentioning
confidence: 99%
“…found evidence for Sulu Sea extension continuing on-shore in northern Borneo by imaging crustal thickness variations using virtual deep seismic sounding. Bacon et al (2022) measured lithospheric anisotropy using XKS splitting and found that orientations of the fast axis of anisotropy were predominantly parallel to the Crocker Range in western northern Borneo, suggesting that anisotropy is dominated by recent continental collision. Fast axis orientations orthogonal to the opening of the Sulu Sea in central northern Borneo further support the idea of Sulu Sea extension propagating on-shore.…”
Section: Introductionmentioning
confidence: 99%